Implementation of public-private partnership projects in the field of healthcare: Problems and prospects - Mityaeva, Natalia V.; Fedorovа, Yulia V. (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. In the current conditions in the healthcare sector, there is an objective real need to develop and implement updated approaches to management, financing and organization of the rendering medical services process. The purpose of the study is to analyze the functioning of PPP mechanisms in the healthcare sector, identify their advantages and limitations, and systematize the experience of implementing PPP projects in practice. Theoretical analysis. The author’s interpretation of public-private partnership in the healthcare sector is given, the strengths of project participants are identified and a categorization of PPP projects in healthcare is proposed, institutional conditions, key parties are analyzed, problems and barriers to the development of PPP in healthcare are identified. Empirical analysis. The most successful experience and main problems of implementing PPP projects in healthcare are analyzed. Results. Applied recommendations are formulated aimed at increasing the efficiency of PPP projects in healthcare. The following are considered as promising mechanisms for the development of PPP projects in the healthcare sector: leasing of existing medical facilities by investors, subject to their equipment and use, creation of mobile medical centers for the population of peripheral areas, signing long-term contracts for medical examinations and check-ups with state clinics, and implementation of medical research aimed at identifying hidden diseases and predispositions.